Analyzing the Discourse on Taglines of Beauty Products in Indonesia - Ichwan Yunus, Ulfa; Ni Gusti Ayu Roselani (Institut Agama Islam Negeri Palopo, 2024)
Discourse on English taglines beauty products play an important role in shaping brand identity and attracting customer attention. This study investigated several English taglines found on logos used by beauty products in Indonesia. This study aims to look at the form, meaning, and function of the language contained in these taglines. The method used in this research was descriptive qualitative. Data collection involved examining English taglines located next to the logo of each beauty product. The results showed that there are 13 English taglines on Indonesian beauty products, 9 taglines are in the form of noun phrases, and 4 taglines are in the form of verb phrases. The meaning of a beauty brand tagline generally illustrates that beauty can increase one's self-confidence and reminds one of the importance of maintaining healthy skin. The language function is analyzed by using Halliday's theory (2004). The language functions in the English tagline are representational and interpersonal. Keywords: Beauty Products, English Tagline, Discourse.